FAKTOR-FAKTOR PENDUKUNG IMPLEMENTASI LEARNING MANAGEMENT SYSTEM (LMS) DALAM MANAJEMEN PENDIDIKAN: SCOPING REVIEW - Jessica Noviana Onggono; Nono Hery Yoenanto; Fitri Andriani (STKIP Pesisir Selatan, 2026)
One manifestation of digitalization within the educational sector is the integration of Learning Management Systems (LMS) into the instructional process. This study aims to synthesize and map the literature on the supporting factors for the successful implementation of LMS. The research employs a scoping review approach, with article selection conducted in accordance with the PRISMA 2020 framework. Based on 14 articles that met the predefined inclusion criteria, five critical success factors for LMS implementation in schools were identified: (1) leadership and institutional management; (2) infrastructure and facilities; (3) teacher acceptance and competence; (4) parental and student support; and (5) school climate. These five factors are pivotal and intrinsically interconnected. The school principal's leadership serves as the primary catalyst for ensuring the sustainability of LMS implementation. Furthermore, teacher competence must be optimized through professional development and balanced by a supportive school climate. Additionally, parental participation and student enthusiasm constitute significant facilitators in the implementation process. These findings imply that an LMS provides schools with the opportunity to transition toward a digital ecosystem by prioritizing school climate, establishing clear LMS policies through effective leadership, and engaging both parents and students to ensure the success of the pedagogical process.